Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Semangat Kerja Guru SMK Swasta Rokita Sari di Yayasan Perguruan Rokita Sari Bangun Purba - Rosniwaty Bangun; Khamo Waruwu; Putri Paramita (STKIP PGRI SITUBONDO, 2021)
In theory, communication affects a person's morale, as well as the environment in which a person works will affect his performance. Researchers want to prove this theory at the Vocational School of the Rokita Sari Bangun Purba Foundation Vocational School. The sample is all teachers in the SMK and multiple linear regression analysis is used to determine the effect of the independent and dependent variables. It was found that communication had a positive and significant effect on morale (sig value 0.000 <0.05), the work environment had a positive and significant effect on morale (sig value 0.001 <0.05), and simultaneously communication and work environment had a positive and significant effect on teacher morale. Rokita Sari Private Vocational School (significance value 0.000 < 0.05)